2017
DOI: 10.1089/fpd.2016.2265
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro and In Vivo Effect of Carvacrol in Preventing Campylobacter Infection, Colonization and in Improving Productivity of Chicken Broilers

Abstract: The current trend in reducing the antibiotic usage in animal production imposes urgency in the identification of novel biocides. The essential oil carvacrol, for example, changes the morphology of the cell and acts against a variety of targets within the bacterial membranes and cytoplasm, and our in vitro results show that it reduces adhesion and invasion of chicken intestinal primary cells and also biofilm formation. A trial was conducted to evaluate the effects of dietary supplementation of carvacrol at four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 32 publications
7
49
0
Order By: Relevance
“…Carvacrol treatment starting 4 days prior murine infection could sufficiently lower intestinal C. jejuni burdens up to 2 orders of magnitude until day 6 p.i. The antimicrobial properties of carvacrol directed against food-borne pathogens such as C. jejuni [26,29,30,37] Salmonella spp. [37,[43][44][45], Escherichia coli O157:H7 [46] and Bacillus cereus [47,48] have been shown in vitro recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carvacrol treatment starting 4 days prior murine infection could sufficiently lower intestinal C. jejuni burdens up to 2 orders of magnitude until day 6 p.i. The antimicrobial properties of carvacrol directed against food-borne pathogens such as C. jejuni [26,29,30,37] Salmonella spp. [37,[43][44][45], Escherichia coli O157:H7 [46] and Bacillus cereus [47,48] have been shown in vitro recently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carvacrol possesses ATPase-inhibiting activity [22,23] and is proposed to act as a proton exchanger that reduces the pH gradient across the cytoplasmic membrane causing changes in proton motive force and in the ATP pool, which leads to cell death [23,24]. Both, in vitro and in vivo studies revealed that carvacrol application could effectively reduce C. jejuni loads in intestinal samples derived from chicken [25][26][27][28]. Furthermore, carvacrol could effectively reduce virulence gene expression and invasion of C. jejuni into chicken cells [26,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Table 1 we have the approach of two articles with in vitro and in vivo analysis, showing important aspects such as reduction in colony formation in Campylobacter sp infected chickens and reduction of Echinococcus granulosus cyst in mice [9,10]. In the Table 2 we have three large areas related to the approach in the studies, firstly effects with anticancer activity being evidenced in four studies, demonstrating cellular apoptosis and reduction of Bcl-2, reduction of gastric cancer with use of nanoparticles, reduction of intestinal lesions, and genotoxicity in lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…A plant‐derived antimicrobial (carvacrol), which can be extracted from oregano oil, was shown to have inhibitory effects for adhesion and invasion of Campylobacter to chicken epithelial cells (Kelly et al., ). When fed (120 to 300 mg/kg feed), it delayed natural colonization by Campylobacter in a 600‐bird study, although cecal counts were similar to control birds by 35 days of age.…”
Section: Interventions Complementary To Biosecurity and Hygienementioning
confidence: 99%